How to develop and sustain a successful pelvic floor MRI practice. - Steiner, Ari; Marks, Robert; Bahrami, Simin; Arif-Tiwari, Hina (Abdominal Radiology, 2021)
Purpose: Magnetic resonance imaging (MRI) of the pelvic floor has become a commonly requested diagnostic tool for pelvic floor assessment. We provide a practical guide for developing, growing, and troubleshooting a dedicated pelvic floor imaging service. Methods: The authors provide an organized approach to the development of a pelvic floor MRI program based on the experience of the SAR Pelvic Floor Disease Focused Panel in academic and private practice settings. Topics addressed include creating interest, staff education, patient preparation both before and after arrival to the imaging center, image acquisition, reporting, and troubleshooting. Results: Using the organization and approach in this guide, the challenge of growing this relatively complex imaging program can be simplified. Familiarity with best practices and established techniques used by successful programs will allow new sites to avoid early pitfalls and quickly develop a mature and autonomous workflow. Conclusions: The development and growing of a pelvic floor MRI program presents its own set of challenges and unique workflow issues which can create anxiety in both patients and providers. We systematically present an approach to streamline the development of a successful pelvic floor MRI program.